2011
DOI: 10.1007/s13593-011-0057-6
|View full text |Cite
|
Sign up to set email alerts
|

Increase in crop damage caused by wild boar (Sus scrofa L.): the “refuge effect”

Abstract: The occurrence of crop damage by wild boars raised dramatically in the last decades, implying an increase in social conflicts, expenditures for compensation and a risk to natural ecosystems. Many researchers have explained this phenomenon by considering wild boar biology, behaviour and abundance. Little or no attention has been devoted to wildlife management and the agricultural mosaic. We hypothesised that the agricultural structure of the landscape and wildlife management planning, including hunting, can pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 25 publications
(46 reference statements)
13
73
0
2
Order By: Relevance
“…In contrast to rural wild boar in our study area, urban wild boar do not use agricultural areas, even though agriculture is available in close proximity to the used habitats (Supplementary Figure 1, Figure 2). Agricultural areas usually provide attractive foraging opportunities for wild boar (Herrero et al, 2006;Amici et al, 2012;Frackowiak et al, 2013;Ficetola et al, 2014). But wild boar are known to be opportunistic omnivores whose diet, in any particular instance, is largely determined by the relative availability of different food types (Schley and Roper, 2003).…”
Section: Habitat Selection In a Landscape Of Fear (Prediction 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to rural wild boar in our study area, urban wild boar do not use agricultural areas, even though agriculture is available in close proximity to the used habitats (Supplementary Figure 1, Figure 2). Agricultural areas usually provide attractive foraging opportunities for wild boar (Herrero et al, 2006;Amici et al, 2012;Frackowiak et al, 2013;Ficetola et al, 2014). But wild boar are known to be opportunistic omnivores whose diet, in any particular instance, is largely determined by the relative availability of different food types (Schley and Roper, 2003).…”
Section: Habitat Selection In a Landscape Of Fear (Prediction 2)mentioning
confidence: 99%
“…Wild boar (Sus scrofa), a social mammal with a growing population throughout Europe (Massei et al, 2015;Keuling et al, 2016), is increasingly present in urban areas (Dinter, 1991;Cahill et al, 2003Cahill et al, , 2012Jansen et al, 2007;Podgorski et al, 2013). Wild boar frequently interfere with people, as they annoy garden owners (e.g., by rooting), can destroy agricultural crops (Amici et al, 2012;Ficetola et al, 2014;Jarolimek et al, 2014;Laznik and Trdan, 2014) and are potential transmitters of zoonotic diseases or diseases relevant to livestock (Fernández et al, 2006;Jansen et al, 2007;Chiari et al, 2015). Therefore, they are a useful model to study the ability of urban wildlife to perceive and respond to spatial variation in the landscape of fear.…”
Section: Introductionmentioning
confidence: 99%
“…The important density in rivers and streams within the study area probably explain that access to water is not a limiting factor in Wallonia. Though the region is relatively flat, we expected that topographic variables, particularly the slope present along the river channel could have been expected to favour wild boar presence, owing to their relative quietness (Amici et al 2012). We attribute the relative weak importance of these variables to the chosen resolution that does not reflect the potential use of these areas, rich in cover and hardly accessible for hunters, as highly suitable for the species.…”
Section: Seasonal Redistributionmentioning
confidence: 99%
“…It has been demonstrated that the absence or banning areas of hunting create a refuge effect favouring the risk of damages to crops (Amici et al 2012). Therefore, an effort on the management and control strategies of wild boar in these landscapes should be promoted.…”
Section: Management Implicationsmentioning
confidence: 99%
See 1 more Smart Citation